1986
DOI: 10.1128/aac.29.4.584
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive high-pressure liquid chromatographic assay for amphotericin B which incorporates an internal standard

Abstract: We developed a rapid, sensitive, high-pressure liquid chromatographic (HPLC) procedure which incorporates a commercially available internal standard, 1-amino-4-nitronaphthalene, to measure amphotericin B in serum. Recovery was quantitative (.90%), and the standard curve was linear from 0.04 to at least 10.0 ,ug/ml. The reproducibility of the assay was good, with intrarun coefficients of variation from 2.0 to 6.8% and interrun coefficients of variation from 4.9 to 10.0%. Comparison by linear regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 19 publications
(25 reference statements)
1
16
0
Order By: Relevance
“…As shown in Fig. 2b (2,6) but is less expensive and time-consuming, and it is at least 10 times more sensitive than the bioassay (1) or simple scanning spectrophotometer methods (18). In agreement with other studies (4), we found that the amount of amphotericin B in the spleen is directly related to the total amount of the drug administered in a 2-week period.…”
Section: * Corresponding Authorsupporting
confidence: 80%
“…As shown in Fig. 2b (2,6) but is less expensive and time-consuming, and it is at least 10 times more sensitive than the bioassay (1) or simple scanning spectrophotometer methods (18). In agreement with other studies (4), we found that the amount of amphotericin B in the spleen is directly related to the total amount of the drug administered in a 2-week period.…”
Section: * Corresponding Authorsupporting
confidence: 80%
“…DAmB (0.5 to 1.5 mg/kg) was administered by constant infusion over 5 min with subsequent sampling of plasma. Sampling times were at 0, 5, 10, 15, 30, and 60 min and 2, 3,4,6,8,12,24,48, and 72 h postinfusion. Infusion of DAmB at dosages of 0.5 to 1.0 mg/kg is well tolerated by rabbits.…”
Section: Animalsmentioning
confidence: 99%
“…Amphotericin B levels in plasma were assayed by highpressure liquid chromatography based upon a modification of the method developed by Granich et al (8). Calibration curves were prepared with plasma with low (25 to 1,000 ng/ml) and high (1 to 20 g/ml) concentration ranges.…”
Section: Animalsmentioning
confidence: 99%
“…In parallel with these recent developments, a need arose for suitable analytical methods to monitor AMB levels in tissue or plasma and thus establish pharmacokinetic and pharmacodynamic relationships. Assays based on in vitro biological activity or chromatographic separations have been described and used to monitor AMB in the circulation (3,11,19,22,23). These methods, however, are characterized by a relatively high limit of detection (Ͼ50 ng/ml) and by technological limitations.…”
mentioning
confidence: 99%